PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PAK CHOI (Brassica rapa) - Emilia S.A. Wangge; Imanuel Sedi Benu (Agriculture Faculty of Flores University, 2012)
This study aims at determining the impact of planting distance on the growth and yield of Pak Choy and determining the optimal distance that can optimize the growth and yield of Pak Choi. This study employed group random design with 6 treatments of planting distance, namelyJ1 = 20 cm x 25 cm, J2 = 20 cm x 20 cm, J3 = Planting distance 20 cm x 15 cm, J4 = Planting distance 20 cm x 10 cm, J5 = 10 cm x 15 cm, J6 = 10 cm x 10 cm.Each treatment was repeated 4 times so that there were 24 specimen garden-beds. It is found out that planting distance did not have any impact on plant height, the width of leaves, and numbers of leaves at age of 10–20 days after planting, whereas there was an impact on plant age of 25–35 days after planting on plant height of 15.59 cm, a number of leaves of 9.17 cm, the width of leaves of 52.28 cm and fresh Pak Choy weight of 148.4g per plant, fresh weight per ha 1204.43 ha.